CONFLICT MANAGEMENT STYLE PADA PASANGAN SUAMI ISTRI YANG TINGGAL BERSAMA MERTUA - Nanda Rossalia; Mohammad Adi Ganjar Priadi (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2018)
When two people get married, they have to adapt each other. Marriage adjustment is necessary for couple so that it will run smoothly. Conflict in a marriage is inevitable. When couple succeed in resolving marriage conflict, it can also improve the quality of marriage. Moreover, people have to do some conflict management style in order adapt and reach good marriage. This phenomenon will be more complicated when couple also live in their parent’s (father and mother in law) house. Based on conflict management theory, there are two types of it; confrontive and avoidant. This research’s aim is to gain conflict management style on couple who live with their parents (father and mother in law). Qualitative method with semi structure interview is used in this research. Participants are couples who live with their parents (father and mother in law) age 18-40 and has been married for 5 years. Result shows three couples has different conflict management style. Furthermore, participants also show conflict with their parents (father and mother in law) paerticularly on parenting style when raise their kids. Couples solve these problem by using two types of conflict, confrontive and avoidant. Result also shows that types of conlict management also depends to vary situation.